2021
DOI: 10.1007/s00167-021-06511-0
|View full text |Cite
|
Sign up to set email alerts
|

Persistent post-operative opioid use following hip arthroscopy is common and is associated with pre-operative opioid use and age

Abstract: PurposeHip arthroscopy utilization continues to increase worldwide. Post‐operative pain management is essential to allow appropriate rehabilitation. While multimodal analgesic protocols have been described, consensus agreement is lacking and opioid analgesia remains a mainstay of treatment. Unfortunately, the risk of persistent opioid use among opioid‐naïve and non‐naïve patients following hip arthroscopy remains unclear. Therefore, the purpose of this study was to identify rates of persistent post‐operative o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…A far higher proportion of patients who used opioids preoperatively went on to request ≥2 more refills after their index arthroscopy, signifying that preoperative opioid use is a marker for potential prolonged opioid use after surgery, allowing for appropriate counseling and cessation efforts before surgery occurs. Our results reinforced what has been shown previously: preoperative opioid use before index hip arthroscopy remains one of the single most important predictors for chronic postoperative opioid use 2 , 11 , 14 , 21 , 50 and is closely tied to patient outcomes. 52 …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A far higher proportion of patients who used opioids preoperatively went on to request ≥2 more refills after their index arthroscopy, signifying that preoperative opioid use is a marker for potential prolonged opioid use after surgery, allowing for appropriate counseling and cessation efforts before surgery occurs. Our results reinforced what has been shown previously: preoperative opioid use before index hip arthroscopy remains one of the single most important predictors for chronic postoperative opioid use 2 , 11 , 14 , 21 , 50 and is closely tied to patient outcomes. 52 …”
Section: Discussionsupporting
confidence: 91%
“…A far higher proportion of patients who used opioids preoperatively went on to request 2 more refills after their index arthroscopy, signifying that preoperative opioid use is a marker for potential prolonged opioid use after surgery, allowing for appropriate counseling and cessation efforts before surgery occurs. Our results reinforced what has been shown previously: preoperative opioid use before index hip arthroscopy remains one of the single most important predictors for chronic postoperative opioid use 2,11,14,21,50 and is closely tied to patient outcomes. 52 In 2020, Beck et al 3 specifically assessed the connection between refills and postoperative outcome, determining that patients requiring more refills had lower patient-reported outcomes and visual analog scale (VAS) satisfaction score averages and higher VAS pain score averages after surgery.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Likewise, Cunningham et al 7 revealed that any opioid use 2 weeks before surgery was the strongest predictor of opioid use after hip arthroscopy. Finally, Degen et al 9 showed that the risk of persistent opioid use (ie, ≥2 prescriptions filled between 9 and 15 months postoperatively) was greatest in patients who used opioids within 1 year before hip arthroscopy. The relationship between preoperative and increased postoperative opioid consumption is generalizable beyond hip arthroscopy as well.…”
Section: Discussionmentioning
confidence: 99%
“…This disregard for less-severe outcomes creates di culty in establishing risk from medically directed opioid use. Moreover, while numerous studies in recent years examined the onset of persistent opioid use (POU) in postsurgical contexts, 31,33,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85] none evaluated the genetic architecture of POU, a gap our study lls. Our analysis of targeted candidate SNPs establishes a clear genetic connection between POU and OUD.…”
Section: Discussionmentioning
confidence: 99%